Pengaruh intellectual capital disclosure, kinerja keuangan, dan kepemilikan manajerial terhadap nilai perusahaan - Muhammad Rivandi (JURNAL PUNDI, 2018)
The achievement of a value of the firm may effect positive impact, both internal and external's company (Debby, Mukhtaruddin, Yuniarti, Saputra, & Abukosim, 2014).This study aims to examine the effect of intellectual capital, financial performance, and managerial ownership on the firm value. The samples of this study are 30 companies listed in Indonesia Stock Exchange selected by using purposive sampling method. Data analysis method used is Multiple regression models. The result this study tested that intellectual capital disclosure have t statistics the biggest than t table (4,137 ≥  1,652), leverage has t statistic the smallest than t table (-0,621 ≤ - 1,652), profitability has t statistic the biggest than t table (2,348 ≤ 1,652) and managerial ownership has t statistic the biggest than t table (2,157 ≥ 1,652). Base on hypothesis tested that the Intellectual Capital Disclosure, Profitability, and Managerial Ownership variable  has Positive a significant effect on the Firm Value, whereas Leverage Variable significant no effect on the Firm Value   Keywords:Intellectual capital disclosure, leverage, profitability, manajerial ownership and firm value